Association between Body Image and Marital Satisfaction in Married Adults - Azra Shaheen,; Uzma Ali,; Haresh Kumar ,; Pirbho Mal Makhija, (Journal of Basic & Applied Sciences, 2016)
Objective: To determine the association between body image and marital satisfaction in married adults. Study Design: A Correlation/ Cross-sectional study Setting and Duration: The study was carried out in Karachi, Pakistan, over a period of three months. Subjects and Methods: The study was conducted after seeking approval from the Board of Advance Studies and Research (BASR), University of Karachi, Pakistan. A total sample of 200 married adults (100 males and 100 females) was selected purposively for the study. The age range of the target group was 22 to 40 years (mean age 34 years; SD=5.13) with minimum of 2 years and maximum of 20 years of marriage. Entire sample had middle socioeconomic status and their education level was from graduation and above. The subject completed the Demographic Information, Multidimensional Body Self-Relations Questionnaire (MBSRQ) and Kansas marital satisfaction scale. Responses were scored according to the producer given in the manuals. Results: Mean ± SD of age was 34.27±7 years. Mean ± SD of duration of marriage is 2 years and 5 months. Significant (P<.05) correlation was found between body image and marital satisfaction among married adults andanalysis of different variables of body image showed that fitness evaluation and body area satisfaction were positively correlated with marital satisfaction while appearance evaluation and subjective weight were negatively correlated. Above body image variables were also found to be significant predictors of marital satisfaction in married adults Conclusion: It is to be concluded that body image is an important predictor in marital satisfaction.